2016
DOI: 10.1016/j.proche.2016.03.125
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of ZnO Nanoparticles Synthesized by Sol-gel Method: A LDA+U Calculation and Experimental Study

Abstract: ZnO nanoparticles were prepared by sol-gel storage method to determine the optimum growth time. The precursor was zinc acetate dihydrate and methanol used as solvent. NaOH act as additive that changes the initial sol pH. The stabilize growth of ZnO nanoparticles was recorded after 12 hours aging time. Structural characterization revealed a single phase of ZnO with hexagonal wurtzite structure. Absorption spectra showed the synthesized ZnO nanoparticles exhibit an optical absorption in visible region. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…In the present investigation, the E g for all the synthesized particles are found to be in the range 3.323-3.4898 eV ( Table 1). As per literature (Harun et al 2016), the E g for ZnO was reported to be 3.37 eV. …”
Section: Structural Analysismentioning
confidence: 62%
“…In the present investigation, the E g for all the synthesized particles are found to be in the range 3.323-3.4898 eV ( Table 1). As per literature (Harun et al 2016), the E g for ZnO was reported to be 3.37 eV. …”
Section: Structural Analysismentioning
confidence: 62%
“…Such agglomeration could be attributed to the extended reaction time. However, the agglomeration in the aqueous medium tends to be more obvious compared to their organic solvent counterpart [16]. This could be due to the fact that organic solvents possessing higher dispersing capability [22].…”
Section: Resultsmentioning
confidence: 99%
“…In any given metal nanoparticles, their properties are a function of their method of synthesis. For the ZnO, various approaches have been used to synthesize them, such as: arc discharge, chemical vapor condensation, hydrothermal, hydrogen plasma-metal reaction, micro emulsion, pyrolysis vapor phase, chemical reduction, sol gel and so on [16][17][18]. As a result of its ability to occur in various convoluted morphologies, it has various unique properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…5), and achieved much improved E g value of ZnO, and these values are close to the experimentally obtained value. [106][107][108] To provide an idea of how DFT calculations can be utilized to estimate the electronic structures and electronic properties of the graphene-based nanocomposites, now we will discuss the DFT calculations of BiFeO 3 -graphene nanocomposite as an example. We have investigated in detail the electronic structures of BiFeO 3 (BFO), graphene, and BFO-graphene nanocomposites by using DFT calculations, with the GGA exchangecorrelation parametrized by PBE.…”
Section: Hubbard-u Schemementioning
confidence: 99%